B-cell profile, B-cell activating factor concentration and IgG levels in human cutaneous and mucosal leishmaniasis - Parodi Ramoneda, Cecilia María (2020)
Aims: The aim of this study was to evaluate characteristics of B cells in human tegumentary leismaniasis (TL) analysing cutaneous leishmaniasis (CL), most prevalent form and mucosal leishmaniasis (ML), aggressive form characterized by the destruction of the oral-nasal-pharyngeal cavities. Methods and results: By flow cytometry analysis, we found decreased percentages of non–class-switched memory B cells in TL with the degree of the loss related to clinical severity. Using commercial ELISA, we reported high levels of B-cell activating factor (BAFF) and IgG preferentially in aggressive CL and markedly in ML together with decreased BAFF receptors in the latter. We also found lower levels of BAFF after clinical recovery suggesting a relation between BAFF and disease activity. Mucosal leishmaniasis history of therapeutic failure presented high levels of BAFF accompanied by detectable concentrations of IFN-γ and IL-6 (assayed by commercial ELISA and cytometric bead arrays respectively), cytokines involved in exaggerated inflammatory responses and tissue damage in TL. Conclusion: We demonstrate B-cell disturbances in TL with the degree of the alterations related to clinical severity. We suggest a relation between excess of BAFF and disease activity and point towards a possible implication of BAFF in the inflammatory phenomenon of ML.